Immune response and long-term clinical outcome in advanced melanoma patients vaccinated with tumor-mRNA-transfected dendritic cells - Kyte, Jon Amund; Aamdal, Steinar; Dueland, Svein; Sæbøe-Larsen, Stein; Inderberg, Else Marit; Madsbu, Ulf Erik; Skovlund, Eva; Gaudernack, Gustav; Kvalheim, Gunnar (Oncoimmunology, 2016)
The most effective anticancer immune responses are probably directed against patient-specific neoantigens. We have developed a melanoma vaccine targeting this individual mutanome based on dendritic cells (DCs) loaded with autologous tumor-mRNA. Here, we report a phase I/II trial evaluating toxicity, immune response and clinical outcome in 31 metastatic melanoma patients. The first cohort (n = 22) received the vaccine without any adjuvant; the next cohort (n = 9) received adjuvant IL2. Each subject received four weekly intranodal or intradermal injections, followed by optional monthly vaccines. Immune response was evaluated by delayed-type hypersensitivity (DTH), T cell proliferation and cytokine assays. Data were collected for 10 y after inclusion of the last patient. No serious adverse events were detected. In the intention-to-treat-cohort, we demonstrated significantly superior survival compared to matched controls from a benchmark meta-analysis (1 y survival 43% vs. 24%, 2 y 23% vs. 6.6%). A tumor-specific immune response was demonstrated in 16/31 patients. The response rate was higher after intradermal than intranodal vaccination (80% vs. 38%). Immune responders had improved survival compared to non-responders (median 14 mo vs. 6 mo; p = 0.030), and all eight patients surviving >20 mo were immune responders. In addition to the tumor-specific response, most patients developed a response against autologous DC antigens. The cytokine profile was polyfunctional and did not follow a Th1/Th2 dichotomy. We conclude that the favorable safety profile and evidence of a possible survival benefit warrant further studies of the RNA/DC vaccine. The vaccine appears insufficient as monotherapy, but there is a strong rationale for combination with checkpoint modulators.